2001
DOI: 10.1161/01.cir.103.6.842
|View full text |Cite
|
Sign up to set email alerts
|

The Gap-Junctional Protein Connexin40 Is Elevated in Patients Susceptible to Postoperative Atrial Fibrillation

Abstract: Atrial myocardium susceptible to AF is distinguished from its nonsusceptible counterpart by elevated connexin40 expression. The heterogeneity of connexin distribution could give rise to different resistive properties and conduction velocities in spatially adjacent regions of tissue, which become enhanced and, hence, proarrhythmic the higher the overall level of connexin40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
3
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(134 citation statements)
references
References 20 publications
11
118
3
2
Order By: Relevance
“…Chemicon, CA, USA), anti-Cx40 (SC-20466; Santa Cruz, CA, USA) and anti-Cx45 (Q14E MAB19-11-5; in-house) [12,13]. Labeled connexin protein was visualized using alkaline phosphatase-conjugated secondary antibody and an NBT/BCIP Liquid Substrate System (Sigma, MO, USA).…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemicon, CA, USA), anti-Cx40 (SC-20466; Santa Cruz, CA, USA) and anti-Cx45 (Q14E MAB19-11-5; in-house) [12,13]. Labeled connexin protein was visualized using alkaline phosphatase-conjugated secondary antibody and an NBT/BCIP Liquid Substrate System (Sigma, MO, USA).…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%
“…Gap junction channels directly link the internal environments of neighboring cardiac myocytes and therefore play a pivotal role in the direct cell-to-cell transfer of the electrical impulses which governs the coordinated contraction of the myocardium [9,10,12] Connexins are the principal components of gap junctions, and three members are expressed in cardiac myocytes: connexin43 (Cx43), connexin40 (Cx40) and connexin45 (Cx45). Disruption of gap junction distribution and remodeling of connexin expression are consistent features of human heart disease [29].…”
Section: Introductionmentioning
confidence: 99%
“…Cx40 is expressed in high levels, 2 to 3 fold higher in the right atrium than the left [46]. It has been shown that the normal Cx40 distribution may also be heterogeneous with areas containing large amounts of Cx40 adjacent to others containing minimal or no Cx40 although hetrogeneities have not been precisely quantified [47][48][49]. The variable expression is likely to lead to inaccuracies in quantification of Cx40 in studies on remodeling in AF since only small samples of right atrial myocardium have been analyzed in most studies.…”
Section: Structure and Function Of Gap Junctionsmentioning
confidence: 99%
“…Due to the difficulty in detecting this connexin (in part due to high cross reactivity of some of the Cx45 antibodies) it has been difficult to determine how much Cx45 is in either normal or pathological atrial tissue although the levels appear to be much lower than either of the other two atrial connexins [46]. The impact of Cx45 on normal function or in atrial fibrillation is not known since it has not been measured in most studies (but see [47]). …”
Section: Structure and Function Of Gap Junctionsmentioning
confidence: 99%
See 1 more Smart Citation